2015
DOI: 10.18632/aging.100854
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of diet-induced hepatic steatosis and hepatic insulin resistance by second generation antisense oligonucleotides targeted to the longevity gene mIndy (Slc13a5)

Abstract: Reducing the expression of the Indy (I'm Not Dead Yet) gene in lower organisms extends life span by mechanisms resembling caloric restriction. Similarly, deletion of the mammalian homolog, mIndy (Slc13a5), encoding for a plasma membrane tricarboxylate transporter, protects from aging- and diet-induced adiposity and insulin resistance in mice. The organ specific contribution to this phenotype is unknown. We examined the impact of selective inducible hepatic knockdown of mIndy on whole body lipid and glucose met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 39 publications
7
52
0
Order By: Relevance
“…Thus, a liver-specific phenotype does not require changes of whole-body fat or body weight. Recent data from another study using RNAi in rats to inhibit mINDY showed similar results [39]. However, that study did not demonstrate specificity or liver-selectivity of the investigated siRNA.…”
Section: Discussionmentioning
confidence: 62%
“…Thus, a liver-specific phenotype does not require changes of whole-body fat or body weight. Recent data from another study using RNAi in rats to inhibit mINDY showed similar results [39]. However, that study did not demonstrate specificity or liver-selectivity of the investigated siRNA.…”
Section: Discussionmentioning
confidence: 62%
“…mINDY‐KO mice gain less weight on a high‐fat diet (HFD) and during the aging process together with lower liver fat content and reduced insulin resistance . Furthermore, we showed that liver‐specific mIndy knockdown using antisense oligonucleotides in adult rats reduced hepatic lipid storage and enhanced hepatic insulin sensitivity upon feeding an HFD . Finally, a competitive, stereosensitive small molecule inhibitor of the mINDY transporter offered complete protection from diet‐induced glucose intolerance in mice and ameliorated diet‐induced fatty liver disease as shown by an independent research group …”
mentioning
confidence: 73%
“…In the liver, the level of cytosolic citrate is well-maintained through CIC-mediated export from the TCA cycle in mitochondria and SLC13A5-mediated uptake from the circulation (24,31). Recent studies reveal that reduced expression of SLC13A5 in mice and rats or its analogues in D. melanogaster and C. elegans resulted in a number of metabolic benefits that either protect mice from HFD-induced obesity and insulin resistance or promote longevity in fruit flies and worms (22)(23)(24)(25)32). Given the emerging significance of SLC13A5 in hepatic energy homeostasis, we sought to determine whether SLC13A5 plays a role in the growth of human hepatoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…The biological importance of SLC13A5 was initially observed in Drosophila melanogaster and Caenorhabditis elegans, in which reduced expression of the SLC13A5 homologues (also named Indy (I'm Not Dead Yet)) extends the life span of both organisms, mimicking caloric restriction (22,23). Reduced expression of SLC13A5 protects mice and rats from high-fat diet (HFD)-induced adiposity and insulin resistance (24,25). On the other hand, up-regulation of SLC13A5 expression was observed in obese, non-alcoholic fatty liver disease patients, HFDtreated rhesus monkeys, and xenobiotic-treated human and rat hepatocytes (26 -28).…”
mentioning
confidence: 99%